A new strong multiple designated verifiers signature. (2nd March 2012) - Tian, H.
A Strong Multiple Designated Verifiers Signature (SMDVS) enables a signer to convince a set of verifiers by generating one signature, of which the verification needs the private key of a verifier. After a brief survey of the current SMDVS schemes and attacks, we found that there were reported or applicable attacks on many schemes, and some schemes needed group communications in the signature verification algorithm. We propose a new SMDVS scheme which is secure against current attacks and needs no extra group communications in the verification algorithm. The scheme is proven secure in the random oracle model.